The new aspects of digitalization in the professional activity of teachers of secondary educational institutions of sports orientation - Shkatova K.M.; Balaeva O.E. (Theory and Practice of Physical Culture, 2025)
Introduction. In modern conditions, the process of digitalization begins to play an important role in the organization of a teacher’s professional activity, i.e. the translation of various types of textual, visual, and information into digitized form. Therefore, the digitalization of education involves filling and improving the digital educational environment, taking into account the requirements of modern realities. The purpose of the study is to determine the role of the digitalization process in the work of a teacher of a professional secondary educational institution in distance and mixed formats. Methodology and organization of research. The object of this study was the teachers of the SPE MSUOR No. 1 and MSUOR No. 3. The methodology of a specific sociological study was used to analyze the problem. This allowed us to obtain more detailed information on the problem under study. First of all, the survey method was used, which was used to obtain primary sociological information. The results of the study and their discussion. Approximately half of the teachers from MSDS No. 1 and MSDS No. 3 conduct their lectures using presentations, and only 1/10 of them use electronic resources in their work, that is, they accompany their lecture with visual materials using electronic resources such as audio, video and photo files. It was also important to study which electronic resources teachers use to implement the learning process. We found out that all teachers are actively working with the «MASH» resource, which allows them to give grades, set homework, and conduct thematic planning of the educational process. It is mandatory for use in public educational institutions: schools and colleges, however, there is no possibility of communication between students and teachers in this resource. Teachers also use LMS electronic educational resources in their work. Tests and exam papers with the transition to a distance learning format have also begun to be conducted using new electronic resources. Previously, about 50% of teachers preferred the ticket form of control, but in the last two academic years, the options of "setting up a vending machine, according to accumulated assessment" prevail. More than 40% of the teachers answered this way. The answers are also popular: "online conversation exam" and online knowledge control tests. Conclusions. Summarizing the information obtained in the course of this study, the authors have created a table that clearly demonstrates the changes in the main aspects of the work of the educational institutions of the ISDR No. 1 and ISDR No. 3 in the context of the intensification of the digitalization process caused by the transition to a distance learning format.